2014
DOI: 10.1016/j.devcel.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin and Its Regulation: On the Logic of X-Shaped Chromosomes

Abstract: The X shape of chromosomes is one of the iconic images in biology. Cohesin actually connects the sister chromatids along their entire length, from S phase until mitosis. Then, cohesin's antagonist Wapl allows the separation of chromosome arms by opening a DNA exit gate in cohesin rings. Centromeres are protected against this removal activity, resulting in the X shape of mitotic chromosomes. The destruction of the remaining centromeric cohesin by Separase triggers chromosome segregation. We review the two-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
149
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 120 publications
(208 reference statements)
4
149
0
Order By: Relevance
“…The anaphase-promoting complex or cyclosome (APC/C), along with its activator cell division cycle 20 (Cdc20), indirectly activates the protease separase through triggering the ubiquitination and degradation of the separase inhibitors, securin and cyclin B1 (3)(4)(5). Active separase then cleaves cohesin, leading to chromosome segregation (6,7). The separated chromatids are evenly partitioned into the two daughter cells through their attachment to the spindle.…”
mentioning
confidence: 99%
“…The anaphase-promoting complex or cyclosome (APC/C), along with its activator cell division cycle 20 (Cdc20), indirectly activates the protease separase through triggering the ubiquitination and degradation of the separase inhibitors, securin and cyclin B1 (3)(4)(5). Active separase then cleaves cohesin, leading to chromosome segregation (6,7). The separated chromatids are evenly partitioned into the two daughter cells through their attachment to the spindle.…”
mentioning
confidence: 99%
“…Cohesin dynamics on chromosomes are regulated by a set of accessory proteins, including the Scc2-Scc4 loading complex and the releasing complex comprising Pds5 and winged apart-like protein (Wapl) (2,4,5). Scc2-Scc4 promotes the loading of cohesin onto chromosomes in telophase and G1 (15).…”
mentioning
confidence: 99%
“…WAPL appears to play multiple roles in the cell, which can vary between organisms and between mitosis and meiosis (Haarhuis et al, 2014). Studies in yeast and animal cells have shown that WAPL in conjunction with PDS5 plays an important role in regulating the reversible binding of cohesin to chromosomes (Bernard et al, 2008;Sutani et al, 2009;Chan et al, 2012;LopezSerra et al, 2013).…”
Section: Proper Cohesin Levels Are Essential For Meiotic Chromosome Smentioning
confidence: 99%